Immunogenicity and Safety of an Inactivated Trivalent Split Influenza Virus Vaccine in Young Children with Recurrent Wheezing - Bae, E. Young (American Society for Microbiology, 2013)
Influenza virus vaccination is recommended for children, but so far, active vaccination has not been achieved because most parents lack knowledge of vaccine safety and many doctors are reluctant to administer vaccine due to concerns that steroids might alter immunogenicity. The aim of this study was to compare the immunogenicity and safety of inactivated trivalent split influenza virus vaccine between children with recurrent wheezing and healthy children of the same age group. Sixty-eight healthy children and 62 children with recurrent wheezing took part in this study. Seroconversion rates, seroprotection rates, geometric mean titers (GMTs), and geometric mean titer ratios (GMTRs) were measured by a hemagglutination inhibition assay for the assessment of immunogenicity. Solicited and unsolicited local and systemic adverse events were measured for the assessment of safety. Regarding immunogenicity, the seroconversion and seroprotection rates showed no difference overall between healthy children and children with recurrent wheezing. Also, no difference was observed between steroid-treated and nontreated groups with recurrent wheezing. Generally, the GMTs after vaccination were higher in the one-dose vaccination groups for healthy children and children with recurrent wheezing, but the GMTRs revealed different results according to strain in the two groups. Regarding safety, solicited local and systemic adverse events showed no differences between healthy children and children with recurrent wheezing. This study demonstrates that inactivated split influenza virus vaccine is able to induce protective immune responses in healthy children, as observed in previous studies, as well as in children with recurrent wheezing who require frequent steroid treatment.